If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+1)=10
We simplify the equation to the form, which is simple to understand
6(x+1)=10
Reorder the terms in parentheses
+(+6x+6)=10
Remove unnecessary parentheses
+6x+6=+10
We move all terms containing x to the left and all other terms to the right.
+6x=+10-6
We simplify left and right side of the equation.
+6x=+4
We divide both sides of the equation by 6 to get x.
x=0.66666666666667
| 50=2.9 | | h=2.9 | | X^/2=1,44 | | -4y+2.5=-4.8 | | 6(x+1)=10-(x-3) | | (2x^0/10x^-3y^2)^2 | | 5x+3=x+2 | | x/4-x/2=9-x | | 4(3x+5y+2z)+3(x-y)= | | 3x^2+28=20x | | 2(x-3)=11(x-21) | | 7g+(3g+4h)= | | 9x=2(2x-5) | | 4x+19=3x-8 | | 3x-2/2-1-4x/3=5 | | x+6=46-x | | -3x-6=-7x+26 | | -3x+5=-29-5x | | -4-6x=5x+7 | | -9-2x=6x+39 | | 3(y+2)=4y-5 | | 3x+7y=2050 | | (x-5)(y+5)=300 | | 9x-9=10x+30 | | m-2n=5 | | 8x-7=5x-4 | | -4x+9=6x-11 | | 5=x+3/2 | | 5x-2=34+2x | | 82=4p+10 | | 6c=3c+10 | | 9x+11=8x+24 |